Prepubertal vulvovaginitis - Salwa Mohammed Neyazi (Wolters Kluwer Medknow Publications, 2019)
Vulvovaginitis is one of the most common gynecologic complaints in prepubertal girls. It accounts for 40%-80% of visits to pediatric gynecology services. It arouses parental anxiety because of the perceived rarity of vulvovaginitis in children, the fear of sexual abuse or concerns over lack of appropriate supervision, and hygiene in daycare or school. The majority of cases are due to nonspecific vulvovaginitis in which vaginal cultures will grow organisms considered to be part of the normal flora. The condition is easily managed with good perineal hygiene. In reluctant cases, oral antibiotics or local estrogen cream may be helpful. A small percentage will have a specific etiology and vaginal cultures will identify the pathogen. Most of these pathogens will be intestinal organisms, respiratory organisms, or sexually transmitted diseases. The isolation of sexually transmitted organisms should alert the physician to investigate for child sexual abuse. Other causes of prepubertal vulvovaginitis include systemic illness and foreign bodies which will result in foul-smelling bloody discharge most commonly toilet paper which can be removed by in-office vaginal irrigation but requires a cooperative child otherwise we may have to do vaginoscopy under general anesthesia.